Pengaruh Brand Ambassador Dan Brand Experience Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variabel Intervening Pada Perusahaan E-Commerce Shopee Di Kota Denpasar - Puspita, Anak Agung Made Erika Dara; Trarintya, Mirah Ayu Putri; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of brand ambassadors and brand experience on purchasing decisions with brand image as an intervening variable. This research was conducted at Shopee e-commerce in Denpasar City. The population in this study are active Shopee users, with a total sample of 110 respondents. The data analysis technique used is validity test, reliability test, path analysis and sobel test. The research results show; Brand ambassador has no significant effect on brand image. Brand ambassador has no significant effect on purchasing decisions. Brand experience has a significant positive effect on brand image. Brand experience has a significant positive effect on purchasing decisions. Brand image has a significant positive effect on purchasing decisions. Brand ambassadors have an indirect effect on purchasing decisions through brand image. Brand experience has an indirect effect on purchasing decisions through brand image.